CULTURAS E PRÁTICAS DO COTIDIANO: METAFORIZANDO COM VISUALIDADES NA BUSCA DE SENTIDOS DO APRENDER…PESQUISAR…ENSINAR - Tourinho, Irene (Paralelo 31, 2016)
O texto propõe o uso de imagens como metáforas para alargar reflexões sobre culturas e as práticas do cotidiano do aprender, do pesquisar e do ensinar. Ao usar diferentes imagens de ‘escadas’, ‘janelas e tijolos’ e ‘sombras’ como metáforas aos desafios e incertezas presentes na atuação de um professor, o texto discute o emprego de metáforas visuais como exercício para práticas e cotidianos pedagogicamente impertinentes, atrelados a zonas de liberdade ousadas e, sempre, eticamente íntegras. CULTURES AND THE PRACTICES OF EVERYDAY LIFE: METAPHORIZING WITH VISUALITIES IN SEARCH OF MEANINGS FOR LEARNING... RESEARCHING...TEACHING Abstract: The paper proposes the use of images as metaphors which can help develop reflection about cultures and the practices of everyday life concerning learning, researching and teaching. In employing diverse images of ‘ladders’, ‘windows and bricks’, and ‘shadows’ as metaphors for challenges and uncertainties present in the performance of teachers, the text discusses the use of visual metaphors as an exercise with everyday practices that is pedagogically impertinent, linked to audacious freedom zones and which are always straightforward ethically.